PROXIMATE ANALYSIS AND NUTRITIONAL PROFILE OF FISH FEED BASED ON DRIED TUBIFEX WORMS (Tubifex sp.) AND PAPAYA LEAF EXTRACT - Wahidi, Budi Rianto; Hafidz, Muhammad Fernanda Pratama; Insivitawati, Era (Universitas Airlangga, 2025)
This study aimed to analyze the nutritional content of fish feed with a novel formulation, combining dried Tubifex worms and papaya leaf extract, to enhance growth and production efficiency in freshwater fish. Proximate tests revealed significant differences between fresh and papaya leaf extract-enriched dried Tubifex worms. Although the protein content of dried Tubifex worms was lower, the addition of papaya leaf extract potentially improved nutritional efficiency through proteolytic enzymes. Dried Tubifex worms enriched with papaya leaf extract offer advantages in storage, buoyancy, and nutritional efficiency, making them a promising feed alternative in aquaculture. Further research is needed to validate their effectiveness at a culture scale.